Diagnóstico de las condiciones y organización laboral de los trabajadores del Área Agropecuaria de la Espam MFL - Fernández Cevallos, Galo Orlando (2013)
Diagnosing the conditions of occupational health and work safety with regards to agricultural workers of the ESPAM MFL, is the principle objective of this research, which aims to contribute to the improvement of the quality of working conditions for these workers. Three stages will be defined in the development of the diagnosis. The matrix FODA, allowed us to identify the internal and external aspects of the population of agricultural workers of the ESPAM MFL that were evident and offered an acceptable assessment of the agricultural area, along with the competitive position of this area, with respect to the institution. The evaluation is done through a survey about the internal factors that affect the productive capacity of the workers, of which the results permit the development of other tools that function in evaluating the labor risks through the application of a graphic scale, with the objective being to measure the efficiency and efficacy of job performance. The matrix of labor risk evaluation contributed in establishing which risks have the greatest impact in the development of everyday labor activities of each worker, grouping them in three: moderate, important and intolerable; identifying all the actions and aspects of the prevailing conditions and work. The proposal is to design a plan of action, involving directors and administrators that will contribute to the counteracting of labor risks.